Effect of botulinum Toxin-A in myofascial pain in temporomandibular disorders: A randomized, double-blinded, placebo-controlled study - Amit Gupta; Anju Aggarwal; Anurag Aggarwal (Indian Journal of Pain, 2016)
Introduction: The temporomandibular disorders (TMDs) include a heterogeneous group of clinical conditions affecting the stomatognathic system and its related structures. It is characterized by pain specific to the maxillofacial region, and these disorders are the main cause of chronic facial pain and disability. Management of TMDs is challenging due to the unknown etiology and complex anatomy of the temporomandibular joint region. Aim and Objectives: To evaluate the effect of botulinum toxin type-A (BTX-A) on pain and day to day functional and social activities of myofascial pain with or without TMDs, and to compare the effectiveness of BTX-A with a placebo group with the aid of EMG and a Behavioural Questionnaire. Materials and Methods: The study was done on 24 patients randomly divided into two groups and each group contains 12 participants. The study group showed a statistically significant decrease in the muscle activity after 14 days, and the patients responded that there was a significant reduction in the pain and improvement in their day-to-day functional as well as social activities after BTX-A treatment with 8 months follow-up. Conclusion: BTX-A has been proven to have positive desired effects on patients with TMDs.